Risk factors for recollapse of the augmented vertebrae after percutaneous vertebroplasty for osteoporotic vertebral fractures with intravertebral vacuum cleft. Issue 2 (January 2017) - Yu, Weibo; Liang, De; Yao, Zhensong; Qiu, Ting; Ye, Linqiang; Huang, Xuecheng; Jiang, Xiaobing
Abstract : Abstract: To determine risk factors related to recollapse of the augmented vertebrae after percutaneous vertebroplasty (PVP) for osteoporotic vertebral compression fractures (OVCFs) with intravertebral vacuum cleft (IVC). Fifty-two patients treated with PVP for single OVCFs with the IVC were retrospectively reviewed. The follow-up period was at least 2 years. Vertebral height loss ≥15% or kyphotic angle ≥10° at the final follow-up in relation to the immediately postoperative values were adopted as a definition of recollapse of the augmented vertebrae. Correlation analysis and multiple logistic regression analyses were performed to elucidate the related clinical or radiological factors for recollapse of the augmented vertebrae including age, gender, bone mineral density, preoperative fracture severity, locations of IVC sign, distribution patterns of polymethylmethacrylate (PMMA), reduction rate, and reduction angle. Assuming the increase of height loss more than 15% as a criterion of recollapse, only cleft filling pattern of PMMA in the IVC area was a significant risk factor for recollapse of the augmented vertebrae ( P  < 0.01). Assuming ≥10° progression of kyphotic angle as a criterion, cleft filling pattern of PMMA and higher values of reduction angle was as 2 significant risk factors for recollapse of the augmented vertebrae ( P  < 0.01). No significant difference was found in other clinical and radiological factors ( P  > 0.05). Cleft filling pattern of PMMA and higher values of reduction angle may play an important role in inducing recollapse of the augmented vertebrae after PVP for OVCFs with the IVC. Careful observation of patients with these conditions is necessary to prevent deterioration of their clinical course.